PERAN PESANTREN DALAM TRANSFORMASI SOSIAL - Nursyaidah, Nursyaidah (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2013)
This work tries to elevate pesantren’s role of alternative Islamic education institution in empowering society to get enlighten. The actualization of this role encourages pesantren to acknowledge societies problems accurately. As a result, pesantren needs to rethink of adhered values and tradition to have more contextual concepts. Through this process which really educates and process moral as the ultimate principal, we expect to spread fundamentally and able to assort people to have a yeaning society, that is independent, wealthy and civilized.